Determinants of brand loyalty in the apparel industry: A developing country perspective - Aobakwe Ledikwe (Cogent Business & Management, 2020)
The study aims to investigate the determinants of brand loyalty in the apparel industry of Botswana. A descriptive quantitative design was followed, and data were collected from respondents using a self-administered questionnaire. A structured equation modelling technique was used to validate the hypotheses. The results indicated an array of positive significant relationships between brand awareness, brand image, brand trust, and brand loyalty. Additionally, brand commitment significantly moderated the influence of brand trust on brand loyalty. Therefore, it is important for the management of apparel brands to cultivate the levels of brand awareness, brand image, brand trust, and brand commitment in order to strengthen brand loyalty and, in turn, contribute to the longevity of apparel brands in Botswana.
Keywords: 650; brand awareness; brand image; brand trust; brand commitment; brand loyalty